The effects of short-term aerobic training program in a hot And cold environment on thermoregulation, sweat Secretion and composition - Sirisinghe, Roland Gamini (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2005)
The effect of low-intensity exercise 1n the heat on thermoregulation and some biochem~cal changes in temperate and tropical subjects under poorly and well-hydrated states was examined. Two V02m£L-c matched groups of subjects consisting of 8 Japanese (JS) and 8 Malaysians (MS) participated in this study under two conditions. They are poorly-hydrated (no water was given) and well-hydrated (3 rnl. Kg-1 body weight of water was provided at onset of exercise, 15th, 35th and 55th min of exercise). Experimental room in both countries was adjusted to a constant level (Ta: 31.5±0.03°C, rh: 72.9±0.1 %). Subjects spent an initial 10 min rest, 60 min of cycling at 40% V02max and then 40 min recovery in the experimental room. Rectal temperatures (Tre) skin temperatures (Tsk), heart rate (HR), heat-activated sweat glands density (HASG), local sweat rate (Msw-back) and percent dehydration were recorded during the test. Blood samples were analysed for plasma glucose and lactate levels. The extent of dehydration was significantly higher in the combined groups of JS ( 1.43± 0.08%) con1pared to MS (1.15±0.05%). During exercise Msw-back was significantly higher in JS compared to MS in the well-hydrated condition. The HASG was significantly more in JS compared toMS at rest and recovery. Tre was higher in MS during the test. Tsk was significantly higher starting at the 5th of exercise until the end of the recovery period in MS compared to JS. In conclusion, tropical natives have lower Msw-back as a result of higher Tsk and Tre during test. However, temperate natives have higher Msw-bock and thus both Tsk and Tre, were lower during experiments in the hot environment. This phenon1enon occurs in both poorly-hydrated and well-hydrated states at low intensity of exercise in hot environ1nent. The difference in Msw-bnck Tsk and Tre, is probably due to vasodilation which occurred during passive heat exposure in tropical natives.